2013
DOI: 10.1117/12.2035098
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of wavefront coding imaging with rotational and non-rotational symmetric phase masks

Abstract: Wavefront coding enables conventional optical imaging systems to operate over an extended depth of field/focus by modifying the light field using a specially designed phase mask. Different phase masks can be used to alter the transmitted wavefront of the optical system which may result in different performances in terms of the capability of the depth-of-focus extension, aberration suppression and the process of imaging acquirement. In this paper, we present a comparative study on the performances of two major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Secondly, the wavefront coded optical system is effectively becoming defocus invariant. Research has shown that the wavefront coding technique with CPM can extend much larger DOF than other phase masks such as the quartic phase mask and the logarithmic phase mask 7 . This is a great advantage on improving functionality of the existing system by using CPM.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the wavefront coded optical system is effectively becoming defocus invariant. Research has shown that the wavefront coding technique with CPM can extend much larger DOF than other phase masks such as the quartic phase mask and the logarithmic phase mask 7 . This is a great advantage on improving functionality of the existing system by using CPM.…”
Section: Introductionmentioning
confidence: 99%